Potassium isotope compositions of carbonaceous and ordinary chondrites: Implications on the origin of volatile depletion in the early solar system - Bloom, Hannah; Lodders, Katharina; Chen, Heng; Zhao, Chen; Tian, Zhen; Koefoed, Piers; Pető, Mária K.; Jiang, Yun; Wang (王昆), Kun (Geochimica et cosmochimica acta, 2020)
Among solar system materials there are variable degrees of depletion in moderately volatile elements (MVEs, such as Na, K, Rb, Cu, and Zn) relative to the proto-solar composition. Whether these depletions are due to nebular and/or parent-body (asteroidal or planetary) processes is still under debate. In order to help decipher the MVE abundances in early solar system materials, we conducted a systematic study of high-precision K stable isotopic compositions of a suite of whole-rock samples of well-characterized carbonaceous and ordinary chondrites. We analyzed 16 carbonaceous chondrites (CM1-2, CO3, CV3, CR2, CK4-5 and CH3) and 28 ordinary chondrites covering petrological types 3– 6 and chemical groups H, L, and LL. We observed significant K isotope (δ41K) variations (−1.54 to 0.70‰) among the carbonaceous and ordinary chondrites. In general, the two major chondrite groups are distinct: The K isotope compositions of carbonaceous chondrites are largely higher than the Bulk Silicate Earth (BSE) value, whereas ordinary chondrites show K isotope compositions that are typically lower than the BSE value. Neither carbonaceous nor ordinary chondrites show clear/resolvable correlations between K isotopes and chemical groups, petrological types, shock levels, cosmic-ray exposure ages, fall/find occurrence, or terrestrial weathering. Importantly, the lack of a clear trend between K isotopes and K content among chondrites indicates that the K isotope fractionations were decoupled from the relative elemental K depletions, which is inconsistent with a single-stage partial vaporization or condensation process to account for these MVE depletion patterns among chondrites. The range of K isotope variations in the carbonaceous chondrites in this study is consistent with a four-component (chondrule, refractory inclusion, matrix and water) mixing model that is able to explain the bulk elemental and isotopic compositions of the main carbonaceous chondrite groups, but requires a fractionation in K isotopic compositions in chondrules. We propose that the major control of the isotopic compositions of group averages is condensation and/or vaporization in pre-accretional (nebular) environments that is preserved in the compositional variation of chondrules. Parent-body processes, such as aqueous alteration, thermal metamorphism, and metasomatism, can mobilize K and affect the K isotopes in individual samples. In the case of the ordinary chondrites, the full range of K isotopic variations can only be explained by the combined effects of the size and relative abundances of chondrules, parent-body aqueous and thermal alteration, and possible sampling bias.